Biosorptive Removal of Cadmium(II) and Copper(II) Using Microwave-Assisted Thiourea-Modified Sorghum bicolor Agrowaste. (10th February 2020) - Salman, Muhammad; Rehman, Rabia; Farooq, Umar; Tahir, Anum; Mitu, Liviu
Abstract : Sorghum bicolor (S.B.) is used in this work for preparing chemically modified adsorbent for toxic metal ions, i.e., cadmium(II) and copper(II). Thiourea is selected for chemical modification of this plant waste by microwave solid fusion methodology, so that its chelating ability for metal ions can be enhanced in both acidic and basic conditions, in a cheaper and quicker way. Characterization was carried out by different physiochemical means using FT-IR, SEM, etc. An increase in pHpzc value was observed in TSB, which is confirmed by FT-IR analysis. The effect of biosorption process parameters was also studied and found that maximum removal of these toxic ions occurred in slightly acidic pH (5-6) conditions, following pseudo-second-order kinetic model. Boyd plots indicated that film dispersion mode was the rate-determining step. Langmuir model indicated that the maximum metal ion removal capacity of TSB was 17.241 mg/g and 15.151 mg/g for cadmium(II) and copper(II) ions. So, TSB can be used on a larger scale for toxic metal ion removal by Sorghum bicolor waste in a cleaner way.